A preliminary survey of non-volant small mammals in the UiTM Negeri Sembilan Forest Reserve, Kuala Pilah Campus / Nur Rabiatul Adawiyah Gazali ... [et al.] - Gazali, Nur Rabiatul Adawiyah; Abdul Rahim, Nursyazni; Marfur, Nur Liyana; Ramli, Nur Hasyimah (UiTM Cawangan Negeri Sembilan, 2022)
Human activities such as agricultural expansion, deforestation and excessive logging have caused a great disturbance toward composition of non-volant small mammals' communities within different types of habitats. Thus, this study is conducted to do a survey on a composition of non-volant small mammals in UiTM Forest Reserve in 2020 and 2021. Cage traps were used to capture the small mammals along the jungle trekking site by locating each trap about 20 m apart along with Capture- Recapture method. Then, the identification process and morphological measurement were conducted. As a result, only one species (six individuals) of non-volant small mammal was captured in 2020 without any sample was recorded in 2021. No sign of destruction detected in the same sampling area in 2021. Other than that, Length-Weight Regression analysis (LWRs) on Tupaia glis measured in 2020 shows a positive allometric (b>3) growth with the value of 'a' and 'b' is -0.581 and 3.672, respectively. These findings suggest that when the weight of the Tupaia glis sample increases, it gets longer. As recommendation, further study should be conducted by prolong the period of sampling and increase in number of cage traps to ensure more samples of non- volant small mammals can be captured.